The experience of MAS in the operation and maintenance of aero-gas turbine engines / Mohamed Saiful Hady Ahmad and Azirul Fahmie Soid - Ahmad, Mohamed Saiful Hady; Soid, Azirul Fahmie (1995)
This project was carried out to research the experience of MAS in operation and maintenance of aero gas turbine engine. There are many departments in MAS. Bat most of the departments is out of our scope of work. Due to this we have made a decision to study on one department. This department is at AERO which stands for Aircraft Engines Repair Operation. This is where all the major and minor operations and maintenance of aero gas turbine engines takes place. From the title of this project we can see that the main objective which is how the aero gas torbine engine is maintained , when the maintenance should be carried out and bow the operation of maintenance of aero gas turbine engines takes place in MAS (the distribution of work in AERO, who is doing what ). This project is regarding of both the maintenance and operation in AERO. We have combined both of this in order to reach our main objective. We have made three phases in order to understand this project easier. In this project, we have inserted quite a number of pictures. Since this is one of the only way that we could share the experience of MAS (AERO )in maintenance -and operation of acrogas turbine engine. Although no attempt is made to describe the equipment and procedures to maintain in detail, several excellent references are presented to aid the reader seeking this type of information. Hope fully this report will be of valuable information to those who has interest in this field.